Aluminum-doped cadmium sulfide homojunction photoelectrode with optimal film quality and water-splitting performance. Issue 7 (6th March 2023) - Zhang, Jiangwei; Yu, Fei; Yu, He; Yang, Shuhui; Zhang, Gaotian; Jiang, Feng; Zhang, Menglong; Luo, Dongxiang
Abstract : The impact of CdS:Al interlayer in MoS2 /CdS photoanode on PEC performance is studied. The CdS:Al interlayer allows improved photocurrent and suppressed dark current. The film chemical features of MoS2 /CdS:Al/CdS photoanode is optimized. Abstract : The electronic band configuration and film quality are two crucial factors of photoelectrodes for conducting photoelectrocatalytic reactions with high efficiency and stability; thus, they need to be rationally designed. In this work, a CdS/CdS:Al-based photoanode is prepared to simultaneously enhance the optimized band structure and film quality. In this architecture, the migration of holes from the light-harvesting component (CdS) to the reduction sites (counter electrode) is inhibited, accompanied with the construction of a desirable transport path for photogenerated electrons to the reduction sites. These features consequently result in the following characteristics: rapid charge separation, a low resistance, a suppressed dark current, and an optimized onset potential. In addition, in the presence of a CdS:Al layer, the in situ grown CdS presents a reduced crystal size, enhanced hydrophilicity, and optimized film continuity. Meanwhile, density functional theory calculations (DFT) reveal that the hydrogen evolution reaction (HER) activity is enhanced after adding CdS:Al as an insertion layer. Thus, an improved MoS2 /CdS:Al/CdS photoanode with high promise is achieved, demonstrating a photocurrent density in the electrolyte with a sacrificial agent of up to 7.9 mA cm −2 (at 0 V vs. V Ag/AgCl ), an on-set potential of −1.23 V ( vs. V Ag/AgCl ), good stability, and an almost totally suppressed dark current.